Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Snrnp25 is a candidate for the peri-implantation lethal phenotype of the Hba deletions - Ana María Velásquez-Escobar; Andrew E. Hillhouse; Terry Magnuson; David W. Threadgill (Mammalian Genome, 2025)
Mutations in adult hemoglobin alpha genes in humans lead to blood disorders commonly known as α-thalassemia. In search of a mouse model for this disease, mutagenesis screens have identified several deletions that resemble these phenotypes. The Hba b2(th) deletion, in particular, replicates the characteristics of alpha-thalassemia minor in heterozygous mice but presents a homozygous embryonic lethal phenotype. Previous analyses of Hba b2(th) mice suggested that the deletion affects both Hba genes ( Hba-a1 and Hba-a2 ) and considered epidermal growth factor receptor ( Egfr ) or rhomboid 5 homolog 1 ( Rhbdf1 ) to be responsible for the embryonic lethality. Molecular analysis of Hba b2(th) revealed a deletion spanning a 1 cM region of mouse chromosome 11. Importantly, the Hba b2(th) deletion does not extend to Egfr , indicating that the observed lethality of homozygous embryos is not due to the loss of Egfr . Sequence analysis of the Hba b2(th) deletion showed that the Hba-a2 gene is not deleted, but the lack of expression is likely due to the disruption of upstream regulatory regions. Furthermore, we identify Snrnp2 5, which codes for the small nuclear ribonucleoprotein 25 (U11/U12), as the candidate gene most likely responsible for the peri-implantation lethality of Hba b2(th) homozygous mice. These findings enhance the understanding of the genetic mechanisms underlying α-thalassemia and provide insights into novel genes essential for early mammalian development.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

The mutant mouse resource and research center (MMRRC) consortium: the US-based public mouse repository system - Yuksel Agca; James Amos-Landgraf; Renee Araiza; Jennifer Brennan; Charisse Carlson; Dominic Ciavatta; Dave Clary; Craig Franklin; Ian Korf; Cathleen Lutz; Terry Magnuson; Fernando Pardo-Manuel de Villena; et al. (Mammalian Genome, 2024)
Now in its 25th year, the Mutant Mouse Resource and Research Center (MMRRC) consortium continues to serve the United States and international biomedical scientific community as a public repository and distribution archive of laboratory mouse models of human disease for research. Supported by the National Institutes of Health (NIH), the MMRRC consists of 4 regionally distributed and dedicated vivaria, offices, and specialized laboratory facilities and an Informatics Coordination and Service Center (ICSC). The overarching purpose of the MMRRC is to facilitate groundbreaking biomedical research by offering an extensive repertoire of mutant mice that are essential for advancing the understanding of human physiology and disease. The function of the MMRRC is to identify, acquire, evaluate, characterize, cryopreserve, and distribute mutant mouse strains to qualified biomedical investigators around the nation and the globe. Mouse strains accepted from the research community are held to the highest scientific standards to optimize reproducibility and enhance scientific rigor and transparency. All submitted strains are thoroughly reviewed, documented, and validated using extensive scientific quality control measures. In addition, the MMRRC conducts resource-related research on cryopreservation, mouse genetics, environmental conditions, and other topics that enhance operations of the MMRRC. Today, the MMRRC maintains an archive of mice, cryopreserved embryos and sperm, embryonic stem (ES) cell lines, and murine hybridomas for nearly 65,000 alleles. Since its inception, the MMRRC has fulfilled more than 20,000 orders from 13,651 scientists at 8441 institutions worldwide. The MMRRC also provides numerous services to assist researchers, including scientific consultation, technical assistance, genetic assays, microbiome analysis, analytical phenotyping, pathology, cryorecovery, husbandry, breeding and colony management, infectious disease surveillance, and disease modeling. The ICSC coordinates MMRRC operations, interacts with researchers, and manages the website (mmrrc.org) and online catalogue. Researchers benefit from an expansive list of well-defined mouse models of disease that meet the highest scientific standards while submitting investigators benefit by having their mouse strains cryopreserved, protected, and distributed in compliance with NIH policies.

The Mutant Mouse Resource and Research Center (MMRRC): the NIH-supported National Public Repository and Distribution Archive of Mutant Mouse Models in the USA - James Amos-Landgraf; Craig Franklin; Virginia Godfrey; Franziska Grieder; Kristin Grimsrud; Ian Korf; Cat Lutz; Terry Magnuson; Oleg Mirochnitchenko; Samit Patel; Laura Reinholdt; K. C. Kent Lloyd (Mammalian Genome, 2022)
The Mutant Mouse Resource and Research Center (MMRRC) Program is the pre-eminent public national mutant mouse repository and distribution archive in the USA, serving as a national resource of mutant mice available to the global scientific community for biomedical research. Established more than two decades ago with grants from the National Institutes of Health (NIH), the MMRRC Program supports a Consortium of regionally distributed and dedicated vivaria, laboratories, and offices (Centers) and an Informatics Coordination and Service Center (ICSC) at three academic teaching and research universities and one non-profit genetic research institution. The MMRRC Program accepts the submission of unique, scientifically rigorous, and experimentally valuable genetically altered and other mouse models donated by academic and commercial scientists and organizations for deposition, maintenance, preservation, and dissemination to scientists upon request. The four Centers maintain an archive of nearly 60,000 mutant alleles as live mice, frozen germplasm, and/or embryonic stem (ES) cells. Since its inception, the Centers have fulfilled 13,184 orders for mutant mouse models from 9591 scientists at 6626 institutions around the globe. Centers also provide numerous services that facilitate using mutant mouse models obtained from the MMRRC, including genetic assays, microbiome analysis, analytical phenotyping and pathology, cryorecovery, mouse husbandry, infectious disease surveillance and diagnosis, and disease modeling. The ICSC coordinates activities between the Centers, manages the website (mmrrc.org) and online catalog, and conducts communication, outreach, and education to the research community. Centers preserve, secure, and protect mutant mouse lines in perpetuity, promote rigor and reproducibility in scientific experiments using mice, provide experiential training and consultation in the responsible use of mice in research, and pursue cutting edge technologies to advance biomedical studies using mice to improve human health. Researchers benefit from an expansive list of well-defined mouse models of disease that meet the highest standards of rigor and reproducibility, while donating investigators benefit by having their mouse lines preserved, protected, and distributed in compliance with NIH policies.

Centralized mouse repositories - Leah Rae Donahue; Martin Hrabe de Angelis; Michael Hagn; Craig Franklin; K. C. Kent Lloyd; Terry Magnuson; Colin McKerlie; Naomi Nakagata; Yuichi Obata; Stuart Read; Wolfgang Wurst; Andreas Hörlein; et al. (Mammalian Genome, 2012)

A novel mouse Smad4 mutation reduces protein stability and wild-type protein levels - Yijing Chen; Della Yee; Terry Magnuson (Mammalian Genome, 2006)

The mouse PcG gene eed is required for Hox gene repression and extraembryonic development - Jianbo Wang; Jesse Mager; Elizabeth Schnedier; Terry Magnuson (Mammalian Genome, 2002)

Toward the yeastification of mouse genetics: chemical mutagenesis of embryonic stem cells - Yijing Chen; John Schimenti; Terry Magnuson (Mammalian Genome, 2000)

Molecular and genetic analysis of the mouse homolog of the Drosophila suppressor of position-effect variegation 3-9 gene - Scott Bultman; Terry Magnuson (Mammalian Genome, 2000)

Genealogy of the 129 inbred strains: 129/SvJ is a contaminated inbred strain - David W. Threadgill; Delia Yee; Argabin Matin; Joseph H. Nadeau; Terry Magnuson (Mammalian Genome, 1997)

SSLPs to map genetic differences between the 129 inbred strains and closed-colony, random-bred CD-I mice - David W. Threadgill; Aragabin Matin; Delia Yee; Minerva M. Carrasquillo; Kenneth R. Henry; Karen G. Rollins; Joseph H. Nadeau; Terry Magnuson (Mammalian Genome, 1997)